Study on Deformation Characteristics of Extended Highway in Operation Period - Pengfei Zhou; Lizhuang Cui; Xuesen Zhang; Chuanyi Ma; Jian Liu; Yanni Shao; Gaohang Lv; Quanyi Xie (Advances in Civil Engineering)
Highway widening has become an effective way to improve the carrying capacity of existing expressways. However, assume that the differential settlement between the new and the old subgrades is not controlled. In that case, it will lead to longitudinal cracks on the pavement, which will seriously affect the safety of vehicles. In this study, the variations of elastic modulus and dynamic elastic modulus of new and old subgrades under traffic load were studied by tests. A hyperbolic model of dynamic elastic modulus increasing with strain is proposed. The numerical calculation model of new and old subgrades under traffic load is established. The deformation characteristics of new and old subgrades without treatment measures and setting up geogrid and geocell are studied. The main conclusions are as follows: (1) with the increase of traffic load and subgrade depth, the elastic modulus changes significantly in the early stage and small in the later stage. (2) Under the condition of no treatment measures, the vertical and horizontal deformation of the subgrade surface show a trend of increasing and then decreasing with the distance from the center line of the subgrade. (3) Setting geogrid and geocell can effectively reduce the differential settlement of the old and new subgrades. (4) The effect of setting geogrid to reduce the differential settlement of old and new subgrades is better than that of setting geogrid.